Evolutionary divergence of photoprotection in the green algal lineage: a plant‐like violaxanthin de‐epoxidase enzyme activates the xanthophyll cycle in the green alga Chlorella vulgaris modulating photoprotection. Issue 1 (16th June 2020) - Girolomoni, Laura; Bellamoli, Francesco; de la Cruz Valbuena, Gabriel; Perozeni, Federico; D'Andrea, Cosimo; Cerullo, Giulio; Cazzaniga, Stefano; Ballottari, Matteo
Summary: The xanthophyll cycle is the metabolic process by which the carotenoid violaxanthin is de‐epoxidated to zeaxanthin, a xanthophyll with a crucial photoprotective role in higher plants and mosses. The role of zeaxanthin is still unclear in green algae, and a peculiar violaxanthin de‐epoxidating enzyme was found in the model organism Chlamydomonas reinhardtii . Here, we investigated the molecular details and functions of the xanthophyll cycle in the case of Chlorella vulgaris, one of the green algae most considered for industrial cultivation, where resistance to high light stress is a prerequisite for sustainable biomass production. Identification of the violaxanthin de‐epoxidase enzyme in C .  vulgaris was performed by genome mining and in vitro analysis of the catalytic activity of the gene product identified. The photoprotective role of zeaxanthin was then investigated in vivo and in isolated pigment‐binding complexes. The results obtained demonstrate the functioning, even though with a different pH sensitivity, of a plant‐like violaxanthin de‐epoxidase enzyme in C .  vulgaris . Differently from C .  reinhardtii, zeaxanthin accumulation in C .  vulgaris was found to be crucial for photoprotective quenching of excitation energy harvested by both photosystem I and II. These findings demonstrate an evolutionary divergence of photoprotective mechanisms among Chlorophyta.